Circuit class therapy or seven‐day week therapy for increasing rehabilitation intensity of therapy after stroke (CIRCIT): a randomized controlled trial. Issue 4 (19th March 2015) - English, Coralie; Bernhardt, Julie; Crotty, Maria; Esterman, Adrian; Segal, Leonie; Hillier, Susan
<x xml:space="preserve">Abstract</x> Background Increased therapy has been linked to improvements in functional ability of people with stroke. Aim To determine the effectiveness of two alternative models of increased physiotherapy service delivery (seven‐day week therapy or group circuit class therapy five days a week) to usual care. Method Three‐armed randomized controlled trial with blinded assessment of outcome. People admitted with a diagnosis of stroke, previously independently ambulant and with a moderate level of disability were recruited. 'Usual care' was individual physiotherapy provided five‐days a week. Seven‐day week therapy was usual care physiotherapy provided seven‐days a week. Participants in the circuit class therapy arm of the trial received physiotherapy in group circuit classes in two 90‐min sessions, five‐days a week. Primary outcome was distance walked on the six‐minute walk test at four‐weeks post‐randomization. Results Two hundred eighty‐three participants were randomized; primary outcome data were available for 259 (92%). In the seven‐day arm participants received an additional three hours of physiotherapy and those in the circuit class arm an additional 22 h. There were no significant between‐group differences at four‐weeks in walking distance (P = 0·72). Length of stay was shorter for seven‐day (mean difference −2·9 days, 95% confidence interval −17·9 to 12·0) and circuit class participants (mean difference −9·2 days, 95% confidence interval −24·2 to 5·8) compared to usual care, but this was not significant. Conclusions Both seven‐day therapy and group circuit class therapy increased physiotherapy time, but walking outcomes were equivalent to usual care.